2008
DOI: 10.1128/aac.00151-08
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of GyrA Amino Acid Required for Ciprofloxacin Resistance in Klebsiella pneumoniae Isolates in China

Abstract: Resistance to ciprofloxacin was detected in 111 (48.1%) isolates of Klebsiella pneumoniae from China. GyrA alterations were identified in the ciprofloxacin-resistant and ciprofloxacin-susceptible isolates. The results, including previously published data, indicate that the single substitution Ser833Ile and three types of double mutations at Ser83 and Asp87 were required for ciprofloxacin resistance (P < 0.05).Resistance to fluoroquinolones is increasing in Klebsiella pneumoniae strains. Mechanisms of resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
10
3
Order By: Relevance
“…Several reports have shown5, 6 that changes in the structure of the QRDRs in gyrA and parC are one of the significant mechanisms in conferring a resistance to fluoroquinolone in gram negative bacilli. The mutations of Ser83 with Phe, Ile, Tyr and Leu is frequently displayed in K. pneumoniae in some studies 5, 30. However, the results from this study suggested the mainly existence of Ser83-Thr alteration in K. pneumoniae isolates, which may be simply due to the investigation of a new population, since most reports have focused on human clinical isolates or bovine mastitis.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Several reports have shown5, 6 that changes in the structure of the QRDRs in gyrA and parC are one of the significant mechanisms in conferring a resistance to fluoroquinolone in gram negative bacilli. The mutations of Ser83 with Phe, Ile, Tyr and Leu is frequently displayed in K. pneumoniae in some studies 5, 30. However, the results from this study suggested the mainly existence of Ser83-Thr alteration in K. pneumoniae isolates, which may be simply due to the investigation of a new population, since most reports have focused on human clinical isolates or bovine mastitis.…”
Section: Discussioncontrasting
confidence: 52%
“…The mutations of Ser83 with Phe, Ile, Tyr and Leu is frequently displayed in K. pneumoniae in some studies. 5 , 30 However, the results from this study suggested the mainly existence of Ser83-Thr alteration in K. pneumoniae isolates, which may be simply due to the investigation of a new population, since most reports have focused on human clinical isolates or bovine mastitis. In this study, it was found that in the Ciprofloxacin-resistant K. pneumoniae , the mutation of the 80th site in the bacterial parC gene was commonly accompanied by the mutation of the gyrA gene, and when parC gene and gyrA gene mutated the sites together, the Ciprofloxacin-resistance rate increased significantly, the results indicating that mutations of parC gene and gyrA gene will make K. pneumoniae more highly resistant to Ciprofloxacin.…”
Section: Discussionmentioning
confidence: 68%
“…Mutations in specific sites in genes coding for proteins used as targets for antimicrobials, such as GyrA and ParC, can result in decreased drug sensitivity. Kp13 showed the double substitutions Ser83 → Phe and Asp87 → Asn in GyrA (KP00955) which are known to confer ciprofloxacin resistance [ 50 ]. Also, a single amino acid change, Ser80 → Ile, was detected in ParC (KP02784), and the combined effect of these mutations could have contributed to the high-level resistance to quinolones displayed by Kp13 as has been shown for other pathogenic bacteria [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…In K. pneumoniae isolates, point mutations in DNA gyrase A (GyrA), plasmid partition protein (ParC), or multidrug efflux pump (AcrA) may be associated with fluoroquinolone resistance [22] , [23] , [24] . In this study, we systematically investigated single nucleotide substitutions in three plasmids from 206 clinical isolates, and found a large amount of nonsynonymous mutations.…”
Section: Discussionmentioning
confidence: 99%